(untitled) (Res Medica, 2014)
It is a great honour and pleasure for me to be invited to this meeting, commemorating the introduction by your former member, T. Lauder Brunton, of amyl nitrite as a potent remedy for anginal pain, one hundred years ago. For some years, I have been interested in the haemodynamic consequences of coronary heart disease, the most common cause of anginal pain. That this symptom is due to an improper balance between the myocardial demand for energy and the supply available from the coronary circulation has been more or less generally accepted for a long time. This view seems, for instance, to have been held by Allan Burns in his book on cardiology printed in this city in 1809. The exact cause of the pain is still uncertain. It seems, however, to be linked to inadequate delivery of oxygen to the myocardium, either generally or locally. And metabolic studies (Cohen el al. 1965) have indicated changes probably due to hypoxia in patients with coronary heart disease not only during but also in the intervals between attacks of angina pectoris. If reduction of the coronary circulation and abnormal metabolism are common in these patients, it is reasonable to expect a reduction in ventricular function as well. However, one of the main symptoms of impaired left heart function, namely dyspnoea, has not been generally regarded as a feature of this condition (P. Wood 1953).